(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The biosynthesis of nickel ferrite (NiFe2O4) nanoparticles is investigated in this work using an aqueous extract of neem (Azadirachta indica) leaves as a natural capping agent. The antibacterial properties of the nanoparticles are assessed in vitro against Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus epidermidis. Active substances including flavonoids, alkaloids, terpenoids, saponins, steroids, and tannins were confirmed by phytochemical screening to be present in the neem extract, indicating their possible function in the creation and stability of nanoparticles. Using a green process that involved calcination and metal salt reduction, NiFe2O4 nanoparticles were created, and their structural characteristics were described using SEM, FTIR, and UV-Vis studies. FTIR verified the presence of organic surface functional groups and Ni–Fe–O bonding, while UV-Vis spectroscopy demonstrated distinctive d-d transitions. SEM pictures showed micro-sized crystalline morphology. Using disc diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) experiments, antibacterial activity was evaluated. Broad-spectrum antibacterial activity was demonstrated by both neem extract and NiFe2O4 nanoparticles, with the nanoparticles showing larger inhibition zones. When compared to neem extract, NiFe2O4 showed better potency, with MIC and MBC against S. aureus and P. aeruginosa as low as 25 mg/mL. These results imply that NiFe2O4 nanoparticles mediated by Neem may be excellent options for antibacterial uses, especially against species of bacteria that are resistant. We make use of neem leaves extract as capping agent to control the synthesis of the NiFe2O4 nanoparticle and explore significant in vitro potential application against S.epidermidis, P.aeruginosa, E. coli, and salmonella typhi.